Hydrodynamic Study of Compressor and Gas Lift Oil Wells - Mammadova, G.G.; Ismayilov, Sh.M. (Herald of Azerbaijan Engineering Academy, 2023)
The article comments on the results of the hydrogasodynamic study of compressor and gas lift oil wells. If no artificial impact method is applied in the oil field, then the process of fountain drilling of wells takes 4-5 years, and compressor and gas lift wells can operate for 8-10 years, and they are transferred to the rod depth pump operation. The structure of the Q = Q (V) curve of compressor and gas lift wells and its character points are explained in detail. A method for constructing indicator diagrams for these wells using the Q = Q (V) curves and methods for determining the hydrodynamic parameters of the formation have been proposed. The results of the survey of gas lift wells in the Sand Island and Gunashli offshore oil fields were analyzed and examined, and the minimum and maximum consumption rates of compressed working agents injected into the wells were determined. It has been shown that as a result of such work it is possible to determine the different features between these two wells.